Supporting Stroke Patients’ Mobility: The Importance of Range of Motion Training in Physical Recovery - Mega Nur Wulandari; Yayuk Ernawati; Yurike Septianingrum; Siti Nur Hasina (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke is a cerebrovascular disease caused by cerebral infarction, characterized by focal neurological deficits lasting more than 24 hours, impaired physical mobility, such as muscle weakness and decreased muscle function, often occurs in stroke patients and worsens their condition, one of the effective recovery steps is Range of Motion (ROM) exercises, which help improve muscle and joint flexibility and prevent muscle contractures, ROM functions to improve muscle strength, coordination, and balance in stroke patients. The purpose of this study was to analyze the action of Range of Motion (ROM) exercises on Muscle Strength in Stroke Patients. methods This study used a systematic review method with PRISMA guidelines. Journal searches were conducted using the keywords stroke, range of motion exercises, ROM applications, and post-stroke recovery through the PubMed, Science Direct, and Google Scholar databases for publications in 2020–2024. Articles were screened based on title and abstract to obtain relevant results. The journals used were in English or Indonesian and met the inclusion criteria, namely open access, discussing non-hemorrhagic stroke, with participants aged over 30 years. Results. From the selection of journals that meet the criteria, 10 journals were selected for further review. The results showed that ROM can increase muscle strength, joint flexibility, and reduce muscle stiffness in stroke patients. Conclusion. ROM exercises have a significant impact on the recovery of stroke patients' mobility by increasing muscle strength, joint flexibility, and quality of life. These exercises are recommended to be done routinely under medical supervision.